The Effect of Prophylactic Nepafenac 0.1% Eye Drops on Macular Changes after Phacoemulsification in Non- Proliferative Diabetic Retinopathy Patients Using Spectral Domain Optical Coherence Tomography (SD-OCT) - Soefiandi Soedarman; Ari Djatikusumo; Syska Widyawati; Arini Setiawati (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: To evaluate the effect of prophylactic nepafenac eye drops on macular thickness changes after phacoemulsification surgery in mild to moderate NPDR patients. Method: This study is an open label randomized clinical trial. Thirty-six subjects who met the inclusion criteria underwent phacoemulsification. One group (18 subjects) were given nepafenac 0.1% eye drops and the rest were given placebo. Foveal thickness was measured by SD-OCT before surgery and the fourth week after phacoemulsification. Best corrected visual acuity (BCVA) and degree of inflammation in the anterior chamber were also being assessed. Result: There was a statistically significant increase foveal thickness in the placebo group 4 weeks after phacoemulsification (p=0.022). Clinically, percentage degree of inflammation in anterior chamber in placebo group was higher than nepafenac group (38.9% : 5.6%) but not significantly different between 2 groups (p=0.27). Nepafenac group achieved clinically better BCVA than the placebo group 4 weeks after phacoemulsification, although statistically there was no significant difference between 2 groups (p=0.991). Conclusion: Nepafenac 0.1% eye drops could prevent foveal thickening 4 weeks after phacoemulsification in mild to moderate NPDR patients. Clinically, nepafenac 0.1% eye drops could decrease the risk of inflammation in the anterior chamber, risk of CME, and vision deterioration although did not reach statistically significant. Keywords: Nepafenac, macular thickness, phacoemulsification, retinopathy diabetic